Controlled synthesis of various SrTiO3 morphologies and their effects on photoelectrochemical cathodic protection performance. Issue 14 (15th July 2022) - Kong, Cunhui; Su, Xinyue; Qing, Da; Zhao, Yingna; Wang, Jiansheng; Zeng, Xiongfeng
Abstract: As an n-type semiconductor with typical perovskite structure, SrTiO3 has broad research prospects in photochemical cathodic protection because of its suitable energy band structure. However, there is a lack of research on the effect of SrTiO3 micro morphology on Photoelectrochemical cathodic protection performance. In this paper, a series of SrTiO3 samples with controllable morphology were designed and prepared by changing the ratio of alcohol to water in the solvent, including nanoparticles (NPs), nano ball (NBs), nano rod (NRs), coral stone-like microspheres (CSLMs) and flower-like microspheres (FLMs). The experimental results show that FLMs samples have better photochemical cathodic protection performance. Under the condition of on light, the photocurrent density of FLMs samples reaches 9.2 μA. The photocurrent density of NPs samples is only 2.5 μA. The former is about 3.6 times that of the latter. The open circuit potential of FLMs samples has shifted from −0.18 V to −0.42 V, with a negative shift of 240 mV, while CSLMs samples have only a negative shift of 180 mV. In contrast, FLMs samples have a more negative shift of 60 mV. After four light cycle experiments, the performance of FLMs samples is stable without obvious change.